Micro- and Nano-Plastics Contaminants in the Environment: Sources, Fate, Toxicity, Detection, Remediation, and Sustainable Perspectives - Rashed, Abdulkarim Hasan; Yesilay, Gamze; Hazeem, Layla; Rashdan, Suad; AlMealla, Reem; Kilinc, Zeynep; Ali, Fatema; Abdulrasool, Fatima; Kamel, Ayman H. (MDPI, 2023)
The continuous production and widespread applications of synthetic plastics and their waste present immense environmental challenges and damage living systems. Microplastics (MPs) have become of great concern in various ecosystems due to their high stability and decomposition into smaller fragments such as nano-plastics (NPs). Nevertheless, MPs and NPs can be removed from the environment using several physical, chemical, and microbiological methods. This study presents a comprehensive narrative literature review, which aims to explore the various types of MPs and NPs, their sources, fate, toxicity, and impact on human health and environment. To achieve this aim, the study employed a comprehensive literature review methodology. In addition, it summarizes various methods of sample collection and analysis techniques. Remediation strategies for MPs and NPs removal are assessed and compared. Furthermore, it highlights interlinkages between the sustainable development goals (SDGs)-specifically SDG 14-and plastic pollution. Overall, priority for research and development in the field of MPs and NPs impacts on ecological ecosystems is a must as this will enable the development of scientific polices driven by global collaboration and governance which in turn will develop tools and methodologies that measure the impacts and risk of plastic pollution.
Keywords: degradation of micro and nano-plastics; analysis methods; health and environmental impacts; remediation techniques; sustainable development goals (SDGs); ADVANCED OXIDATION PROCESSES; MARINE-ENVIRONMENT; DYNAMIC MEMBRANE; SKIN PENETRATION; DRINKING-WATER; WASTE-WATER; FRESH-WATER; POLYSTYRENE NANOPARTICLES; POLYMERIC NANOPARTICLES; MICROPLASTIC POLLUTION; Environmental Sciences & Ecology; Water Resources